Strategies to increase teachers' organizational commitment based on local wisdom and organizational support - Linawati, Linawati; Setyaningsih, Sri; Hardhienata, Soewarto; Hartono, Rudi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
Low teacher commitment remains a major challenge in educational management, affecting the consistency of instructional quality and institutional stability. This research aimed to formulate a strategy to strengthen teachers’ institutional attachment by integrating local wisdom and organizational support. The study employed the Modeling and Optimization of Management Resource Strengthening (POP-HR) approach combined with SITOREM analysis to identify key variables and prioritize improvement indicators. Data were collected through a multistage random sampling of 120 foundation-based teachers using standardized questionnaires measuring transformational leadership, career development, and local wisdom values of silih asih (mutual care) and silih asuh (mutual guidance). The results of path analysis showed that transformational leadership and career development had significant direct and indirect effects on teacher loyalty, mediated by cultural values. SITOREM findings revealed several weak indicators such as equality, motivation, and training opportunities that require targeted improvement. Strengthening leadership practices, supporting career growth, and internalizing local cultural values were found to be effective strategies to enhance teacher engagement and dedication. The findings provide a framework for developing culturally grounded strategies in education management to strengthen teacher engagement